Nifty Futures Rollover Strategies - Slivka, Ronald T.; Yang, Jie; Wan, Weiyu (Indian Journal of Finance, 2017)
As expiration dates for Nifty stock index futures approach, trading volume in calendar spreads rises at times to over 50% of the total daily volume, making this transaction particularly important to execute efficiently for investors rolling over sizable positions into deferred month contracts. In this study, futures data covering 12 recent Nifty futures expirations was used for rollover strategy construction, analysis, and testing. We reported here on the comparison of findings for three different strategies: optimally rolling an amount that minimized average calendar spread volatility subject to practical trading constraints, rolling an equal number of Nifty futures daily, and rolling all contracts on a single day. We found, in all cases, that the optimal strategy outperformed the other two commonly employed rollover strategies. Practical guidelines for rolling Nifty futures positions were also discussed.